LOYALITAS MEREK KOMUNITAS PENDAKI GUNUNG: Pengaruh Relasi Merek dan Identifikasi Komunitas dengan Mediasi Keterikatan dan Tekanan Normatif - Rosdiana, Puti; Alif, M. Gunawan (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2018)
This study is researching mountaineers’ community regarding community’s brand loyalty. With 112 samples from four mountain climbing communities in Great Jakarta, this survey measures the variables effect of Brand Relationship Quality, Community Identification, Normative Community Pressure and Community Engagement and its impact toward Community’s Brand Loyalty, adopted from the study of Algesheimer, Dholakia, and Hermann (2005). Hypothesis testing using simple and multiple regressions shows a positive significance influence of Brand Relationship Quality toward Community Identification and Community’s Brand Loyalty. Furthermore, Community Identification has a significance positive influence toward Normative Community Pressure and Community Engagement, but does not have significance effect toward Community’s Brand Loyalty. Similarly, Normative Community Pressure also does not have any effect toward Community’s Brand Loyalty. However, Community Engagement has positive significance influence toward Community’s Brand Loyalty. To cite this article (7th APA style): Rosdiana, P. & Alif, M. G. (2018). Loyalitas Merek Komunitas Pendaki Gunung: Pengaruh Relasi Merek dan Identifikasi Komunitas dengan Mediasi Keterikatan dan Tekanan Normatif [Brand Loyalty among the Mountain Hiker Community]. Journal Communication Spectrum, 8(2), 208-231. http://dx.doi.org/10.36782/jcs.v8i2.1855